Childhood adversity and depression of older adults: the moderating effect of social participation - Wang, Ping; Cheng, Xin; Zhang, Nan; Liu, Huilin (Frontiers in Psychology, 2024)
Objective Examine the effect of childhood adversity on depression in older adults and the regulatory impact that social participation has on depression. Methods Based on 6,704 standard-compliant research subjects, single factor analysis, multiple linear regression model, and tendency score matching were used to analyze the impact of childhood adversity on depression in older adults and the regulatory effect of social participation. Results The depression rate is higher among women, young age, low education, unmarried, in agricultural households, older adults with low annual income, pre-retirement work type in agriculture, non-drinking, and those with two or more chronic diseases(P<0.05). Children who experienced adversity as children are more likely to suffer from depression as adults (β=0. 513,0.590,0.954,0.983,1.221,0.953,0.718; P<0.05). Through the tendency score, the result is matched with the endogenous test. As well, older adults are more likely to suffer psychological damage from a greater number of childhood adversities in their early years (β=1.440,2.646,4.122; P<0.001). It has been shown that social participation will reduce the negative impact of low-income family economic circumstances on depression among older adults of all ages (β=-0.459,-0.567; P<0.01), aggravate depression resulting from "neighborhood void of mutual assistance" and "no more fun to play" for older adults of all ages (β=1.024,0.894; P<0.01), and exacerbate depression resulting from "loneliness because there are no friends" for the oldest old (β=0.476,0.779; P<0.05). Conclusion Older adults who experience childhood adversity are more likely to suffer from depression. Social participation plays a regulatory role in the relationship between childhood adversity and depression in older adults. For older adults' mental health to improve, family and social adversity should be prevented, and moderate participation in society should be encouraged.